A search for 4 specific markers linked to Pm3 alleles for resistance to powdery mildew (Blumeria graminis) in rye (Secale cereale) - Jurkowski, Andrzej; Bujak, Henryk (Biological Letters, 2019)
To investigate powdery mildew resistance in rye (Secale cereale), 397 inbred lines of winter rye were tested for susceptibility to infection with Blumeria graminis f. sp. secalis. The 50 most tolerant lines and 50 most infected lines were chosen for comparison. They were next tested for the presence of 4 markers linked to 4 alleles for resistance to powdery mildew, identified earlier in common wheat (Triticum aestivum). We found Pm3a only in 3 susceptible genotypes of winter rye, although this marker is linked to the powdery mildew resistance gene in wheat. The other 3 markers linked to Blumeria graminis f. sp. secalis resistance genes (Pm3b, Pm3c, Pm3d) were found in neither resistant nor susceptible rye genotypes.